2006
DOI: 10.1002/path.2118
|View full text |Cite
|
Sign up to set email alerts
|

Human airway surface epithelial regeneration is delayed and abnormal in cystic fibrosis

Abstract: Cystic fibrosis (CF) at an advanced stage of the disease is characterized by airway epithelial injury and remodelling. Whether CF remodelling is related to infection and inflammation or due to an abnormal regenerative process is still undecided. We have recently established the expression and secretion profiles of interleukin (IL)-8, matrix metalloproteinase (MMP)-7, MMP-9, and tissue inhibitor of metalloproteinase (TIMP)-1 during non-CF airway epithelial regeneration in a humanized nude mouse xenograft model.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
91
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(107 citation statements)
references
References 55 publications
15
91
1
Order By: Relevance
“…These results may relate to the hyper-proliferative state previously described in CF HAECs (Voynow et al, 2005;Hajj et al, 2007). The rapid onset of proliferation in CF HAECs could be explained, in part, by increased amount of progenitor cells in these cultures.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…These results may relate to the hyper-proliferative state previously described in CF HAECs (Voynow et al, 2005;Hajj et al, 2007). The rapid onset of proliferation in CF HAECs could be explained, in part, by increased amount of progenitor cells in these cultures.…”
Section: Discussionsupporting
confidence: 53%
“…We also evaluated whether KLF4 regulates Cx26 expression in repairing HAECs. Because a hyperproliferative state has been described in CF HAECs (Voynow et al, 2005;Hajj et al, 2007), we investigated the expression of Cx26 and KLF4 in this disease as well.…”
Section: Introductionmentioning
confidence: 99%
“…The human airway epithelium can be fully regenerated in vitro from isolated HAECs maintained in culture in an air-liquid interface condition. 20 In this model, we observed a progressive regeneration of pseudostratified epithelium after 4 to 6 weeks ( Figure 3A). By using immunofluorescence and RT-PCR techniques, we observed that the expression of ␣7 nAChR in the basal layers of the epithelium was maximal in steps II and III (appearance of the first ciliated cells) and paralleled the expression of CK14, a marker of airway basal cells, 29 suggesting that ␣7 nAChR expression in basal cells is essential during the initial step of epithelial differentiation and the establishment of the basal cell layer.…”
Section: ␣7 Nachr Expression Is Associated With the Differentiation Omentioning
confidence: 72%
“…2,19,20 After 5, 7, 9, 11, 16, 23, 30, and 33 days, cells were detached with trypsin and counted with the ADAM-MC apparatus (Labtech, France).…”
Section: Epithelial Cell Isolation and Culturementioning
confidence: 99%
“…28 -30 However, a direct interaction between TIMP-1 and a MMP has not been demonstrated in a physiological model. TIMP-1 expression by epithelial cells increases during epithelial regeneration in various wound-healing and disease models, [31][32][33][34][35][36][37][38] including lung transplantation and during the onset of BOS. 39 -42 Transgenic overexpression of TIMP-1 by keratinocytes delays skin wound closure in vivo, 43 suggesting that the endogenous protein functions to govern re-epithelialization.…”
mentioning
confidence: 99%